P14.25 Hiv and stis among male sex workers attending australian sexual health clinics. (13th September 2015) - Callander, D; Read, P; Minichiello, V; Hamilton, R; Chow, EPF; Ali, H; Lewis, D; Hellard, M; Donovan, B
Abstract : Introduction: The sale of sex by gay, bisexual and other men who have sex with men (GBM) has been identified in many parts of the world as an activity with increased transmission risk for HIV and other STIs. It is, however, unknown if HIV/STI prevalence among male sex workers (MSWs) in Australia is higher than it is among GBM who do not sell sex. This study explores the sexual health of MSWs relative to other GBM attending Australian sexual health clinics (SHCs). Methods: De-identified patient data were extracted from 34 SHC databases in Victoria and New South Wales. A cross-sectional analysis was conducted among MSWs and other GBM at their first visit during 2011–2013. HIV/STI prevalence was calculated as the proportion of diagnosed individuals among those tested. Multivariate logistic regression analyses were used to assess factors associated with HIV and other STIs. Results: A total of 471 MSWs presented at participating SHCs between 2011 and 2013, as well as 24, 833 other GBM. At first visit, 44 (9%) MSWs had known HIV infections while of the 396 men tested there were 10 (3%) new diagnoses. Overall, 50 MSW were diagnosed with a bacterial STI at their first visit: 11% with chlamydia, 6% with gonorrhoea, and 2% with infectious syphilis. Among MSWs, HIV infection was associated with increasing age (p = 0.002) but compared to other GBM, selling sex was not associated with HIV infection (p = 0.9) nor STI diagnoses (p = 0.2). Conclusion: Although prevalence of HIV and other STIs appears to be similar among GBM regardless of whether or not they sell sex, over one in ten MSWs were diagnosed with HIV or an STI. The higher prevalence among this population underscores the need for routine sexual health testing and for future studies to better understand which MSW sub-populations are most at-risk. Disclosure of interest statement: The ACCESS Sexual Health Services Network is funded by the NSW Ministry of Health, Victorian Department of Health, Australian Capital Territory Department of Health, and the Northern Territory Department of Health.